Analisis Implementasi Kurikulum Merdeka dalam pembelejaran Matematika di SMP NU Lekok - Saibah, Hildayatus (Center of Education Journal (CEJou), 2023)
Freedom Learning is a program that is very in line with the agenda of improving the quality of education. By understanding in depth the implementation of the program will certainly make this program be implemented well. Since 2019, the government through the Ministry of Education, Culture, Sports, Science and Technology, conducts an education revolution at elementary, junior high and high school levels by carrying out independence in all aspects of formal education. Freedom Learning means freedom in learning, which is to provide opportunities for learning as freely as possible and as comfortable as possible to students or students to learn calmly, casually, and happy without stress or pressure.Beyond knowledge, hobbies, and special skills, to have a portfolio that suits each existence and essence. Placing the burden on students who are out of their abilities are despicable and impossible to do by a wise teacher. This is like a blind student, the teacher asks him to tell his friends what buffalo is and how the buffalo is. Freedom learning can also be said